Tree-cavity occurrence, cavity occupation and reproductive performance of secondary cavity-nesting birds in oak forests: The role of traditional management practices - Robles, Hugo; Ciudad, Carlos; Matthysen, Erik (Forest Ecology and Management, 2011)
Secondary cavity-nesting birds (SCN), which cannot create their own breeding cavities, are expected to be inﬂuenced by habitat alteration caused by forest management practices, but the mechanisms underlying the distribution pattern of SCN subjected to different management systems are poorly known. To improve our knowledge on these mechanisms, we examine cavity abundance, cavity occupation and reproductive performance of SCN in Pyrenean oak (Quercus pyrenaica) forests subjected to two management systems: (i) dense “young forests”, maintained at such stage by clear-cuttings and burns, and (ii) “old forest”, subjected to extensive traditional grazing and scarce ﬁrewood extraction by selective cutting. Young forests had considerably lower density of cavities (1.29 ± 0.71 vs 15.09 ± 2.00 cavities ha−1 ), SCN species (0.18 ± 0.11 vs 0.61 ± 0.07 species ha−1 ) and nests (0.40 ± 0.27 vs 2.67 ± 0.25 nests of all SCN ha−1 ) than old forests, indicating that a low availability of cavities may limit SCN assemblages in young oak forests. However, reproductive parameters of great (Parus major) and blue (Cyanistes caeruleus) tits associated with the availability of food (laying date, clutch size, nestling number and weight, adult weight) did not differ between both forest types, suggesting that food supply was not reduced in young forests, at least for tits during the breeding season. Large diameter (up to 170 cm dbh) decayed trees were the most likely to hold cavities, but birds preferred smaller living cavity-trees for nesting (90% of nests in 21–65 cm dbh trees). The preservation of cavity-trees within traditionally managed old oak forests is crucial in providing nesting opportunities to SCN. Besides, the protection of these traditionally managed forests would also beneﬁt to other forest organisms that depend on old and open oak forests.
Keywords: Cavity occupation; cavity-nesting birds; Dehesa; Quercus pyrenaica; Reproductive performance; Traditional management